Seroprevalence of influenza D virus in bulls in Argentina - Alvarez, Ignacio J. (2020)
Influenza D virus (IDV) is considered a new agent involved in bovine respiratory disease (BRD). Based on seroprevalence studies or isolation from clinical samples, this virus has been detected on several continents and in several animal species, including cattle, pigs, camel, horses, and goats. We used an indirect in-house ELISA to detect anti-IDV antibodies in 165 serum samples from bulls on 116 farms in the province of La Pampa, Argentina. Eighty-five of 116 (73%) farms had at least 1 positive animal, and 112 of 165 (68%) of the analyzed samples were positive. There were no significant differences in the proportion of seropositive samples depending on the geographic region in which the samples were taken. Our results suggest that IDV infection is endemic in La Pampa; the clinical importance of IDV in Argentina remains to be investigated.